Social vulnerability and health risk: Analysis in culturally diverse agricultural contexts - Hernández-Pedreño, Manuel; Romero-Sánchez, Eduardo; Haz-Gómez, Francisco Eduardo; García-Luque, Olga (Acciones e Investigaciones Sociales, 2021)
Although there is a large body of research that relates social conditions to the levels of infection of covid-19 disease, it has hardly been contextualised in the agricultural setting. Given this gap, this study delves into the social determinants that have an impact on high incidence rates of the pandemic in an agricultural labour context, where a large immigrant population, such as the Murcian municipality of Totana, converges. Based on an action-research methodology, secondary sources of information (review of studies and statistical analysis of databases) are complemented with three primary sources applied to different social agents: a) a survey of workers in a fruit and vegetable company; b) in-depth interviews with representatives of vulnerable households; and c) a discussion group with professionals from different areas of intervention in the face of the socio-health emergency. The results allow us to link the social conditions of the municipality with the lower levels of social protection and, therefore, of pandemic prevention. While the surveyed population shows a medium-high level of knowledge of the risks of the pandemic, the most vulnerable groups have real limitations, derived from deficient socio-occupational and residential conditions. The professionals emphasise that the pandemic has accentuated pre-existing social risks, linked to the strong attraction of seasonal agricultural labour. The study verifies that the precarious employment and residential conditions of a large group of the local population have had an impact on their higher levels of contagion, mainly among foreign nationals, who have fewer family and/or educational resources.